2018
DOI: 10.1175/jcli-d-18-0074.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TC Temperature and Water Vapor Climatologies between the Atlantic and Pacific Oceans from GPS RO Observations

Abstract: Tropical cyclone (TC) temperature and water vapor structures are essential atmospheric variables. In this study, global positioning system (GPS) radio occultation (RO) observations from the GPS RO mission named the Constellation Observing System for Meteorology, Ionosphere, and Climate and the Global Navigation Satellite System (GNSS) Receiver for Atmospheric Sounding on board both MetOp-A and MetOp-B satellites over the 9-yr period from 2007 to 2015 are used to generate a set of composite structures of temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Referring to Yang et al [30], we constructed the TC composite field data based on the collocation criteria of the best track data of TC cases and COSMIC-2 RO profiles during 2020-2021 with a temporal difference of less than 3 h and a radial distance of less than 1000 km from TC centers. The composite analysis technique is the primary approach for TC PBL studies, which provides an overview and characterization of the problem under study.…”
Section: Data Collocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to Yang et al [30], we constructed the TC composite field data based on the collocation criteria of the best track data of TC cases and COSMIC-2 RO profiles during 2020-2021 with a temporal difference of less than 3 h and a radial distance of less than 1000 km from TC centers. The composite analysis technique is the primary approach for TC PBL studies, which provides an overview and characterization of the problem under study.…”
Section: Data Collocationmentioning
confidence: 99%
“…Liu et al [34] pointed out that the LSW is used to characterize the uncertainty of retrieved bending angle and refractivity profiles and proposed an LSW-based quality control procedure for eliminating low-quality data from data assimilation. Using GPS ROs data, Yang et al [30] investigated TC temperature and water vapor structures. Comparing the results before and after quality control, they discovered that the warm-core architectures of TCs would be significantly distorted if outliers were not deleted.…”
Section: Quality Controlmentioning
confidence: 99%
“…Mueller et al [32] suggested that this is mainly attributed to the fact that RO detection can provide a large amount of atmospheric observation data at sea. Yang et al [33] showed that RO data are conducive to the further study of tropical cyclone (TC) temperature and water vapor structures. Liu et al [34] clearly showed that RO is also very helpful for studying TC genesis.…”
Section: Introductionmentioning
confidence: 99%